Quantitative assessment of collateral time on perfusion computed tomography in acute ischemic stroke patients - Xu, Yao; Yang, Jianhong; Gao, Xiang; Sun, Jie; Shang, Qing; Han, Qing; Wu, Yuefei; Li, Jichuan; Xu, Tianqi; Huang, Yi; Pan, Yuning; Parson, Mark W.; et al. (Frontiers in Neurology, 2023)
Background and Aim: Good collateral circulation is recognized to maintain perfusion and contribute to favorable clinical outcome in acute ischemic stroke. This study aimed to derive and validate an optimal collateral time measurement on perfusion computed tomography imaging for patients with acute ischemic stroke.This study included 106 acute ischemic stroke patients with complete large vessel occlusions. In deriving cohort of 23 patients, the parasagittal region of the ischemic hemisphere was divided into 6 pial arterial zones according to pial branches of middle cerebral artery. Within the 85 arterial zones with collateral vessels, the receiver operating characteristic analysis was performed to derive the optimal collateral time threshold for fast collateral flow on perfusion computed tomography. The reference for fast collateral flow was the peak contrast delay on collateral vessel within each ischemic arterial zone compared to its contralateral normal arterial zone on dynamic computed tomography angiography. The optimal perfusion collateral time threshold was then tested in predicting poor clinical outcome (modified Rankin score of 5-6) and final infarct volume in the validation cohort of 83 patients.Results: For the derivation cohort of 85 arterial zones, the optimal collateral time threshold for fast collateral flow on perfusion computed tomography was delay time of 4.04 seconds (area under the curve=0.78 [0.67, 0.89], sensitivity=73%, specificity=77%). Therefore, the delay time of 4 seconds was used to define the perfusion collateral time. In the validation cohort, the perfusion collateral time showed slightly higher predicting power than dynamic computed tomography angiography collateral time in poor clinical outcome (area under the curve=0.72 vs 0.67; P<0.001). Compared to dynamic computed tomography angiography collateral time, the perfusion collateral time also had better performance in predicting final infarct volume (R-squared values= 0.55 vs 0.23; P<0.001).Our results indicate that perfusion computed tomography can accurately quantify the collateral time after acute ischemic stroke.